Simplify the expression -3(4x +5) – 2(-5x +8)

Question

Simplify the expression -3(4x +5) – 2(-5x +8)

in progress 0
Eva 8 hours 2021-09-15T00:52:30+00:00 1 Answer 0

Answers ( )

    0
    2021-09-15T00:53:55+00:00

    Answer:

    x=-31/2

    Step-by-step explanation:

    Let’s equate the equation to zero

    -3(4x+5)-2(-5x+8)=0

    -12x-15+10x-16=0

    Collect like terms

    -12x+10x-15-16=0

    -2x-31=0

    Add 31 to both sides

    -2x=31

    Divide both sides by-2

    x=-31/2

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )